2018
DOI: 10.1111/rge.12172
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Constraints on the Origin of Banded Iron Formation‐Hosted Iron Ore from the Archaean Ntem Complex (Congo Craton) in the Meyomessi Area, Southern Cameroon

Abstract: Banded iron formations (BIFs) are the most significant source of iron in the world. In this study, we report petrographic and geochemical data of the BIF from the Meyomessi area in the Ntem Complex, southern Cameroon, and discuss their genesis and the iron enrichment process. Field investigations and petrography have revealed that the studied BIF samples are hard; compact; weakly weathered; and composed of magnetite, subordinate quartz, and geothite. The geochemical composition of the whole rock reveals that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The craton is made up of various migmatitic gneisses of TTG composition, granitoids, and remnants of greenstone belts commonly made up of pyroxenites, serpentinites, banded iron formations (BIF), mafic and ultramafic metavolcanics, and post-tectonic metadoleritic dykes (Fig. 1; Ganno et al, 2018;Soh et al, 2018). The Paleoproterozoic Nyong unit is considered as one of the oldest subducted oceanic slab or trace of a suture zone recorded within the West Central African Fold Belt (Bouyo et al, 2019).…”
Section: Geographical and Geological Settingsmentioning
confidence: 99%
“…The craton is made up of various migmatitic gneisses of TTG composition, granitoids, and remnants of greenstone belts commonly made up of pyroxenites, serpentinites, banded iron formations (BIF), mafic and ultramafic metavolcanics, and post-tectonic metadoleritic dykes (Fig. 1; Ganno et al, 2018;Soh et al, 2018). The Paleoproterozoic Nyong unit is considered as one of the oldest subducted oceanic slab or trace of a suture zone recorded within the West Central African Fold Belt (Bouyo et al, 2019).…”
Section: Geographical and Geological Settingsmentioning
confidence: 99%
“…In addition, the lack of a greenstone xenolith in the granodiorites suggests that the pluton predates the emplacement of the supracrustal rocks. The greenstone belt formation consists of gabbronoritic gneiss, alternating with banded enderbitic gneisses, amphibolites and deformed banded iron formations (BIF); intruded by high-K granites, syenites and dolerite dyke (Maurizot et al, 1986;Teutsong et al, 2017;Ganno et al, 2018). The BIFs display alternating of Fe-oxide-and silicate-rich layers (Fig.…”
Section: Greenstone Beltmentioning
confidence: 99%
“…The BIFs display alternating of Fe-oxide-and silicate-rich layers (Fig. 2i), metamorphosed into the granulite facies (Ganno et al, 2018). Ndime et al (2019) reported the Pb-Pb whole-rock isotopic date of ca.…”
Section: Greenstone Beltmentioning
confidence: 99%
“…Hydrothermal alteration in the Ntem complex has been recognised by recent works at the vicinities of the study area (in areas subject to advanced mineral exploration works) which also showed that hydrothermalism occurred in the Ntem Complex in a shallow seawater, probably in a subduction context [106] [107] [108] [109]. Porphyry as a subclass of hydrothermal deposits, is associated with one or various intrusions of felsic to intermediate rocks [4] [110] [111] as it is the case in this portion of the Ntem Complex made up of TTG granites, granodiorites [41] [47].…”
Section: Hydrothermal Alteration Mapping and Mining Implicationsmentioning
confidence: 99%